Cordyceps militaris-Fruiting Bodies, Mycelium, and Supplements: Valuable Component of Daily Diet - Karol Jędrejko; Katarzyna Kała; Katarzyna Sułkowska-Ziaja; Agata Krakowska; Piotr Zięba; Krystian Marzec; Agnieszka Szewczyk; Agnieszka Sękara; Jolanta Pytko-Polończyk; Bożena Muszyńska (MDPI AG, 2022)
Cordyceps militaris has long been used in Eastern medicine for alleviating fatigue and as an immunostimulant. The present study aimed to determine the content of biologically active substances (bioelements and organic compounds), the total phenolic content, and the antioxidant activity of fruiting bodies (commercially available and self-cultivated), mycelia, and two food supplements. The results show that substrate composition and cultivation method had an influence on the properties of mushroom materials. An important aspect of the study is the estimation of the content of bioactive substances present after extraction into digestive juices in the artificial gastrointestinal tract model, which can allow for determining the amount of these substances that is potentially bioavailable for the human body. The best results for cordycepin (81.4 mg/100 g d.w.) and lovastatin (53.6 mg/100 g d.w.) were achieved for commercially available food supplements. Furthermore, after digestion in artificial intestinal juice, the highest amount of cordycepin was determined in the fruiting bodies from commercially obtained (25.9 mg/100 g d.w.) and self-cultivated mushroom (25.8 mg/100 g d.w.). In conclusion, the mycelium and fruiting bodies of C. militaris are ideal food supplements and pharmaceutical agents and can serve as a good source of prohealth substances potentially bioavailable for humans.